Lectin‐based phototherapy targeting cell surface glycans for pancreatic cancer. Issue 7 (7th December 2022) - Kuroda, Yukihito; Oda, Tatsuya; Shimomura, Osamu; Hashimoto, Shinji; Akashi, Yoshimasa; Miyazaki, Yoshihiro; Furuya, Kinji; Furuta, Tomoaki; Nakahashi, Hiromitsu; Louphrasitthiphol, Pakavarin; Mathis, Bryan J; Nakajima, Takahito; et al.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is resistant to current treatments but lectin‐based therapy targeting cell surface glycans could be a promising new horizon. Here, we report a novel lectin‐based phototherapy (Lec‐PT) that combines the PDAC targeting ability of rBC2LCN lectin to a photoabsorber, IRDye700DX (rBC2‐IR700), resulting in a novel and highly specific near‐infrared, light‐activated, anti‐PDAC therapy. Lec‐PT cytotoxicity was first verified in vitro with a human PDAC cell line, Capan‐1, indicating that rBC2‐IR700 is only cytotoxic upon cellular binding and exposure to near‐infrared light. The therapeutic efficacy of Lec‐PT was subsequently verified in vivo using cell lines and patient‐derived, subcutaneous xenografting into nude mice. Significant accumulation of rBC2‐IR700 occurs as early as 2 hours postintravenous administration while cytotoxicity is only achieved upon exposure to near‐infrared light. Repeated treatments further slowed tumor growth. Lec‐PT was also assessed for off‐target toxicity in the orthotopic xenograft model. Shielding of intraperitoneal organs from near‐infrared light minimized off‐target toxicity. Using readily available components, Lec‐PT specifically targeted pancreatic cancer with high reproducibility and on‐target, inducible toxicity. Rapid clinical development of this method is promising as a new modality for treatment of pancreatic cancer. Abstract : What's new? Antibody‐conjugated therapies have shown insufficient efficacy against pancreatic cancer. In our study, the authors engineered and tested a lectin‐photoabsorber conjugate that targeted cell‐line and patient‐derived xenograft‐based pancreatic cancer. The conjugate reduced tumor size after near‐infrared light treatment and exhibited minor off‐target effects in a mouse model. The study offers foundational in vitro and in vivo evidence for a novel phototherapy that targets cell surface glycans using a lectin‐based carrier system. With all components readily available, a therapeutic protocol that could greatly enhance treatment of refractory pancreatic cancer could be rapidly developed in the clinic.